Distinctions between the Ancient Islamism and the Contemporary Islamism in Nigeria - Hakeem Olatunji Tijani (PERSPEKTIF, 2022)
The misconception that is woven around Islamism has necessitated the choice of discourse in this chapter. In Nigeria, Islam as a religion is at the center of the misconception because adherents of the religion, today, have adopted a violent method to protect its principles. It has, therefore, become important to analytically unravel the conceptual entanglement between the ancient Islamism and the violent Islamism. The ancient Islamists maintained the Islamic civilisation without inflicting other civilisations, especially the Western. On the contrary, violent Islamists have agitated for a new order that is destructive of other civilisations. This chapter contributes to the ongoing debate in the literature apropos of the conceptual entanglement associated with Islam and Islamism. This chapter is connected to the broader scope of the book as it makes a difference between the acceptable Islamism that accommodates other civilisations, and violent Islamism that embraces violent jihadism (armed struggle with infidels). This is important because the conceptual entanglement has blurred our understanding of Islam with its instrumental values. This chapter uses secondary data to analyse ancient Islamism and the contemporary Islamism that embraces violence in Nigeria. It concludes that Islam is not associated with violence and, analytically, separates the contemporary violent Islamism from the ancient Islamism.